1996
DOI: 10.1016/s0928-8244(96)00074-0
|View full text |Cite
|
Sign up to set email alerts
|

Fimbrial adhesins: similarities and variations in structure and biogenesis

Abstract: Fimbriae are wiry (2 to 4 nm diam.) or rod-shaped (6 to 8 nm diam.), fibre-like structures on the surfaces of bacteria which mediate attachment to host cells. Much has been learned in recent years about the biogenesis, structure and regulation of expression of these adhesive organelles in Gram-negative bacteria. Analyses of the genetic determinants encoding the biogenesis of fimbriae has revealed that the adhesive interaction of fimbriae can be mediated by major subunits (CFA/I and CS1 fimbriae) or minor subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thick helical fimbriae can be stretched under certain in vitro conditions (117) or by using force to unwind the helix (118), accompanied by conformational changes in fimbrial subunits. It has been suggested that fimbrial stretching occurs in vivo to adjust and coordinate the lengths of the few hundred fimbrial threads anchoring the colonizing bacteria that are submitted to the intestinal peristalsis and its resulting shear force (119). Fimbriae-mediated bacterial adhesion to a target cell is enhanced by shear force, as described with F41 fimbriae (120).…”
Section: Fimbrial Structuresmentioning
confidence: 99%
“…Thick helical fimbriae can be stretched under certain in vitro conditions (117) or by using force to unwind the helix (118), accompanied by conformational changes in fimbrial subunits. It has been suggested that fimbrial stretching occurs in vivo to adjust and coordinate the lengths of the few hundred fimbrial threads anchoring the colonizing bacteria that are submitted to the intestinal peristalsis and its resulting shear force (119). Fimbriae-mediated bacterial adhesion to a target cell is enhanced by shear force, as described with F41 fimbriae (120).…”
Section: Fimbrial Structuresmentioning
confidence: 99%
“…Flagellae, pili, fimbriae and outer membrane proteins may all be required for bacterial adhesion [35,36,37,38,39,40,41,42]. Many of these are in the form of proteinaceous filaments with adhesin activity that mediate long-range adhesion during colonization [43,44,45,46]. Expression of these proteins may be regulated to match environmental conditions, which has significant implications for experimental studies of bacterial adhesion, i.e.…”
Section: Mechanisms Mediating Bacterial Adhesionmentioning
confidence: 99%
“…In a previous study, we demonstrated that R. crassostreae have the unusual ability to produce unipolar fimbriae . These types of protein fibrils are important in other bacterial species for surface attachment (Wall and Kaiser, 1999) and the development of biofilms (O'Toole et al, 2000), or in the case of a pathogenic association, to host cells (Smyth et al, 1996). The molecular switch controlling the expression of flagella vs. fimbriae in R. crassostreae is unknown, however elucidation of this mechanism is expected to be important in understanding the early stages of JOD.…”
Section: Discussionmentioning
confidence: 99%